Trauma, psychological distress and markers of systemic inflammation among US women: A longitudinal study. (November 2022) - Lawn, Rebecca B.; Murchland, Audrey R.; Kim, Yongjoo; Chibnik, Lori B.; Tworoger, Shelley S.; Rimm, Eric B.; Sumner, Jennifer A.; Roberts, Andrea L.; Nishimi, Kristen M.; Ratanatharathorn, Andrew D.; Jha, Shaili C.; Koenen, Karestan C.; et al.
Abstract: Background: Prior evidence links posttraumatic stress disorder (PTSD) and depression, separately, with chronic inflammation. However, whether effects are similar across each independently or potentiated when both are present is understudied. We evaluated combined measures of PTSD and depression in relation to inflammatory biomarker concentrations. Methods: Data are from women (n's ranging 628–2797) in the Nurses' Health Study II. Trauma exposure, PTSD, and depression symptoms were ascertained using validated questionnaires. We examined (a) a continuous combined psychological distress score summing symptoms for PTSD and depression, and (b) a categorical cross-classified measure of trauma/PTSD symptoms/depressed mood status (reference group: no trauma or depressed mood). Three inflammatory biomarkers (C-reactive protein [CRP], interleukin-6 [IL-6], tumor necrosis factor alpha receptor 2 [TNFR2]) were assayed from at least one of two blood samples collected 10–16 years apart. We examined associations of our exposures with levels of each biomarker concentration (log-transformed and batch-corrected) as available across the two time points (cross-sectional analyses; CRP, IL-6 and TNFR2) and with rate of change in biomarkers across time (longitudinal analyses; CRP and IL-6) using separate linear mixed effects models. Results: In sociodemographic-adjusted models accounting for trauma exposure, a one standard deviation increase in the continuous combined psychological distress score was associated with 10.2% (95% confidence interval (CI): 5.2–15.4%) higher CRP and 1.5% (95% CI: 0.5–2.5%) higher TNFR2 concentrations cross-sectionally. For the categorical exposure, women with trauma/PTSD symptoms/ depressed mood versus those with no trauma or depressed mood had 29.5% (95% CI: 13.3–47.9%) higher CRP and 13.1% (95% CI: 5.1–21.7%) higher IL-6 cross-sectionally. In longitudinal analysis, trauma/PTSD symptoms/depressed mood was associated with increasing CRP levels over time. Conclusions: High psychological distress levels with trauma exposure is associated with elevated inflammation and is a potential biologic pathway by which distress can impact development of inflammatory-related chronic diseases, such as cardiovascular disease. Considering multiple forms of distress in relation to these pathways may provide greater insight into who is at risk for biologic dysregulation and later susceptibility to chronic diseases. Highlights: High psychological distress with trauma is associated with elevated inflammation. Associations with inflammation are strongest in women with multiple forms of distress. Trauma without distress was not robustly associated with inflammation.